Phototherapy Induced Hypocalcemia in Neonates with Unconjugated Hyperbilirubinemia - Amna Khan; Anila Farhat; Hamayun Anwar; Sajid Shamim; Mujeeb Ur Rehman; Irfan Khan (Journal of Bahria University Medical and Dental College)
Objective: To determine the frequency of hypocalcemia in neonates with unconjugated hyperbilirubinemia receiving phototherapy. Study design and setting: Cross sectional study conducted at neonatal intensive care unit, King Abdullah Teaching Hospital, Mansehra for one year from December 2017 to November 2018. Methodology: Total 213 full term stable neonates of either gender with jaundice were studied in this study. Out of which, 143 with unconjugated hyperbilirubinemia were exposed to phototherapy while 70 neonates with exaggerated physiological hyperbilirubinemia taken as control were not exposed to phototherapy. Serum calcium level was determined through blood test before and after 24 hours of phototherapy. SPSS version 22 was used to analyze the data. Frequency and percentages were used to describe categorical variables like gender and hypocalcemia. Hypocalcemia was stratified by age and gender to see effect modifiers. Post stratified chi-square test was applied in which p value = 0.05 was considered as significance value. Results: In study group, 143 neonates who received phototherapy had mean age of 7 days ± 2.62 SD. Total 65% neonates were male and 35% neonates were female. Mean serum calcium level of neonates before and after provision of phototherapy was 9.28 mg/dl ± 0.23 and 8.54 mg/dl ± 0.68 respectively, which is statistically significant. The frequency of hypocalcemia was 40% in neonates with unconjugated hyperbilirubinemia after 24 hours of phototherapy. Conclusion: Hypocalcemia is an important complication in neonates with unconjugated hyperbilirubinemia after continuous phototherapy. Hypocalcemia has clinical impact and adds to morbidity, and if left untreated, can lead to mortality.